2014
DOI: 10.1177/1541931214581003
|View full text |Cite
|
Sign up to set email alerts
|

A Flight Simulator Study to Evaluate Manual Flying Skills of Airline Pilots

Abstract: This paper reports an experimental study with the objective to assess pilots' raw-data-based flight performance which is affected by long-term practice and structured training. Fifty-seven airline pilots with different levels of aviation experience scheduled on an Airbus fleet, representing contrary levels of practice and training, had to fly a simulated 45 minutes approach and landing scenario while flight performance data were objectively recorded. The level of practice and training was found to have a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…These results stand in contrast to the flight phases Change-Course 1 to 5 that show a significant decrease in performance for the abnormal condition. Therefore, in accordance with previous research (e.g., Haslbeck et al 2014;Taylor et al 2007), we could show that the level of training affects performance in different ways and is dependent on the flight phase. Age differences between the N and P groups cannot explain the decrease in performance between the groups, because there was no age difference between the N and E groups in our sample.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results stand in contrast to the flight phases Change-Course 1 to 5 that show a significant decrease in performance for the abnormal condition. Therefore, in accordance with previous research (e.g., Haslbeck et al 2014;Taylor et al 2007), we could show that the level of training affects performance in different ways and is dependent on the flight phase. Age differences between the N and P groups cannot explain the decrease in performance between the groups, because there was no age difference between the N and E groups in our sample.…”
Section: Discussionsupporting
confidence: 91%
“…Haslbeck et al (2014) assessed raw-data-based flight performance of airline pilots with different levels of experience in a 45-min ILS approach scenario where the participants' performance was measured as deviation from the ideal glide slope and localizer. The results showed that in accordance with other previous research (e.g., Taylor et al 2007;Tsang 2003), a significant influence of practice and training levels confounded with the pilots' age and experience on manual flight operations was observed, necessitating the need for further studies with the inclusion of medium-level groups (Haslbeck et al 2014). The studies above focused on manual aircraft control by analyzing the performance in terms of how the pilots responded in execution.…”
Section: Influences On Manual Flight and Performancementioning
confidence: 99%
“…A limiting factor of our previous research (Haslbeck et al, 2014) was that the different sources of variance (e.g., level of practice, flying experience, and type of aircraft) could not be separated because only A320 FOs had been compared to A340 CPTs. To reach a more conclusive comparison, we included two additional groups, A320 CPTs and A340 FOs, in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Ebbatson, 2009; Franks, Hay, & Mavin, 2014); (b) daily flight practice, addressing on-the-job training (Fleishman, 1966; Savion-Lemieux & Penhune, 2005); and (c) the influence of flight simulator sessions, when periodically selected flying tasks and maneuvers are to be practiced (recurrent training) and tested (proficiency checks) under the supervision of trainers and examiners (Buckley & Caple, 2009). It was hypothesized that with a higher level of practice and training, pilots show better fine-motor flight performance (Haslbeck, Kirchner, Schubert, & Bengler, 2014). Referring to the level of practice and training , a secondary research question arises: whether the time dated back to flight school and expertise (determined by rank) or the daily flight practice (determined by fleet) has a stronger influence on manual flight proficiency.…”
Section: Research Questions and Hypothesesmentioning
confidence: 99%
“…Computerized virtual reality scenario are established in the context of training of various professional figures, for instance, airliner pilots using flight simulators recreating real scenarios ( Haslbeck et al, 2014 ) or virtual trainings for surgeons ( Boyle et al, 2011 ; Ahlborg et al, 2015 ). In this context, personalization of training regimen based on individual characteristics is crucial and it can be used to enhance specific cognitive functions both in healthy individuals and patients, with favorable outcomes in everyday life activities ( Klingberg et al, 2005 ; Jaeggi et al, 2008 ; Alloway, 2012 ; Shinaver et al, 2014 ; Spencer-Smith and Klingberg, 2015 ).…”
Section: Introductionmentioning
confidence: 99%